Competing for keeping a global status: London as a world actor - Simões-Ferreira, Isabel (2017)
Late 20th century has marked the advent of a new metropolitan age: cities’ capacity, especially Western cities’ can do spirit to reinvent themselves in an era of de-industrialization and worlwide fierce competition. Globalization and the weakening of the nation-state have paved the way for the centrality of cities as nodes of spatial and political dynamics, stretching from their cultural influence to their effectiveness in developing trade routes, investments and all sorts of power relations. In this context, the convergence between the spheres of cultural and economic development leads us to think of culture, in Raymond Williams’s words, as “a whole way of life”, a form of lived experience or complex reality of a place, whose dynamics may have impact at a local level (national inter-urban competition) or at a supranational level (setting a global ideological agenda, or, “a politics of place beyond place” to follow Dorey Massey’s argument). Bearing this background in mind, the focus for a more detailed analysis will be put on the renewal of London as a world city, namely from the 1980s onwards. Tracing some of the milestones of London’s reinvention as a world city means looking into a plethora of forces: Thatcherite neoliberal policies, New Labour enterprising culture, the pivotal role of the City, the heart of London’s financial services, the lure of London as a place of opportunities and the creativity dispositif as a form of governmentality, amongst other related issues.